Poetry, Science, and the Epistemological Debate - Picchione, John (TTR)

(untitled) (Association canadienne de traductologie, 1999)
AbstractPoetry, Science, and the Epistemological Debate — The last few decades have witnessed a radical questioning of the cognitive possibilities traditionally associated both with science and literature. This article gives a brief overview of the debate and provides a critique of the deconstructive and post-modern theories in their attempt to subvert fundamental epistemological claims. The article then addresses the specificity of poetic cognition and, distancing itself from mimetic conceptions of poetry, proposes that poiêsis entails a peculiar creation of reality, unattainable with other tools. It is the uniqueness of the materiality of poetic language that contributes to the formation of subjectivity and to the expansion of human reality and consciousness.